Thermal and stress tension dual-responsive photonic crystal nanocomposite hydrogels. Issue 37 (8th July 2019) - Yan, Dan; Lu, Wei; Qiu, Lili; Meng, Zihui; Qiao, Yu
Abstract : Easily prepared dual-responsive optical nanocomposite hydrogel (ONH) sensors which are responsive to tension and temperature are reported. Abstract : Easily prepared dual-responsive optical nanocomposite hydrogel (ONH) sensors which are responsive to tension and temperature are reported in which polymethyl methacrylate (PMMA) colloidal arrays were embedded into the hydrogels to obtain an optical response. Because of the band gap in the photonic crystal (PhC), the bright color of ONHs can be tuned by an external stimulus according to Bragg's law. Thermosensitive N -isopropyl acrylamide (NiPAm) is added to the gel system, and by controlling NiPAm content and temperature, the contraction of the dual-response ONHs and the structural color response in the visible light range can change accordingly. Meanwhile, the temperature responses can be repeated more than seven times. Owing to the high biocompatibility, the excellent temperature response and the good mechanical strength of the ONHs, such optical biosensors have wide application in the biological field as an external stimulus sensor for implantable sensors, intracorporeal pressure measurement, and body temperature detection.